WHAT ARE THE DIFFERENTIATING FACTORS BETWEEN INVESTOR AND SHAREHOLDER INVESTMENT? - Yeni, Fitri; Pitoyo, Rubianto; Afriany, Afriany (Jurnal Riset Akuntansi dan Keuangan, 2024)
This research aims to find out the factors that are considered when making capital allocation decisions during the abnormal capital market period. whether the investors and the shareholders use the same factors to form an investment allocation. This research uses an exploratory factor analysis model to determine variables that can explain the relationship or correlation between various independent indicators that are observed. Findings, theres five factors that investors consider when allocating their investment, and two factors that are used by shareholders. The single index model is the most important factor for investors to determine capital allocation, and Earnings per shareis for shareholders. Beta stock is important factor for inventors and shareholders when making capital allocation. The greater beta stock provides greater expectations of the risks and return This research is expected to assist investors in determining investment valuation methods by considering five factors in order to achieve the highest rate of return and because shareholders are concerned with the long term and the ultimate goal of increasing the value per share, they should consider the growth of earnings per shares and the value of beta stock.